The Possibility of Intervention and Exploitation of Wood Stock of Natural Pure Dense Stand of Brutia Pine (Pinus brutia Ten.) at Braddon Site -Lattakia - AlaAldin, Hassan; Ali, Wael; Dayoub, Rami (Latakia University Journal -Biological Sciences Series, 2013)
The objective of the research is to study the possibility of intervention in natural dense pure stand of brutia pine (Pinus brutia Ten.)located in Rabiya/Lattakia/Syria; and the possibility of exploiting part of wood stock to prevent trees from arriving to a self-thiningphaseresulting from high tree density. A self- thining model and a diameter increment model were used to achieve that. The area under study is about90 hectares. Two different stands can be distinguished: An old stand(45-55 years old) with an area of​​70hectares A youngstand (20-24 years old) with an area of ​​20hectares The young plot resulted from the natural regeneration following the 1988 fire.14 circular sample plots were established with an area of 400 m2 each. The plots were established so that they cover the variation in age and stocking density per unit area. Results showed thatthecurrent density is about97.24% and 101% of max density in old and young stands, respectively, whereas thewood stock volume is 393and325.25m3/ha for old and young stands. Results also indicated that it is possible now toexploit26 and56.4m3/ha of old and young stands, respectively.